2020
DOI: 10.1186/s12958-020-00599-8
|View full text |Cite
|
Sign up to set email alerts
|

Study on follicular fluid metabolomics components at different ages based on lipid metabolism

Abstract: Background: Follicular fluid is an important external environment for the growth and development of oocytes. A thorough identification of specific components in follicular fluid can better the existing understand of intracellular signal transduction and reveal potential biomarkers of oocyte health in women undergoing assisted reproductive therapy. To study on follicular fluid metabolomics components at different ages based on lipid metabolism, we have adopted a new method of SWATH to MRM(the sequential window … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…This reduced fertility can be due to the decline in total number of oocytes and their quality, as well as changes in the surrounding environment such as the FF. Previous studies have shown that possible age-related mechanisms include changes in the antioxidant defences and lipid metabolism in the FF (Luddi et al, 2020;Tatone et al, 2008;Zhang et al, 2020). Oxidative stress alters protein structures (Luddi et al, 2020;Tatone et al, 2008), which may in turn allows more chemicals to pass through the blood-follicle barrier.…”
Section: Chemical Group and Age Affects Chemical Transfer From Blood ...mentioning
confidence: 99%
“…This reduced fertility can be due to the decline in total number of oocytes and their quality, as well as changes in the surrounding environment such as the FF. Previous studies have shown that possible age-related mechanisms include changes in the antioxidant defences and lipid metabolism in the FF (Luddi et al, 2020;Tatone et al, 2008;Zhang et al, 2020). Oxidative stress alters protein structures (Luddi et al, 2020;Tatone et al, 2008), which may in turn allows more chemicals to pass through the blood-follicle barrier.…”
Section: Chemical Group and Age Affects Chemical Transfer From Blood ...mentioning
confidence: 99%
“…The progress of these innovative approaches could help to improving the optimization of mapping and quantifying genes, lipid and protein characterizations. Providing a new method to explore the lipidomic changes in oocyte and embryo development has open insights that hold potential to disentangle the function of lipid metabolism in embryo and oocyte developmental capability in animals (Chen et al., 2020; Zhang et al., 2020). Moreover, understanding the precise embryonic and oocyte lipid profile might contribute to improving the freezing protocol and enhance the cryotolerance of both oocyte and embryo (Zhang et al., 2020).…”
Section: Impacts Of Forskolin On In Vitro Embryo Developmentmentioning
confidence: 99%
“…Providing a new method to explore the lipidomic changes in oocyte and embryo development has open insights that hold potential to disentangle the function of lipid metabolism in embryo and oocyte developmental capability in animals (Chen et al., 2020; Zhang et al., 2020). Moreover, understanding the precise embryonic and oocyte lipid profile might contribute to improving the freezing protocol and enhance the cryotolerance of both oocyte and embryo (Zhang et al., 2020). Further explorations are essential to explore the association between lipids and both embryo quality and sensitivity to cryopreservation in animals.…”
Section: Impacts Of Forskolin On In Vitro Embryo Developmentmentioning
confidence: 99%
“…In the early stage, two projects of National Natural Science Foundation of China have used nontargeted follicular fluid metabolomics based on UHPLC-MS technology to preliminarily screen and explore the biomarkers of kidney qi deficiency syndrome in the elderly [ 15 ]. The study found that the components of follicular fluid in elder women were significantly different from that in younger women.…”
Section: Introductionmentioning
confidence: 99%